Asset Valuation to Determine the Company Zakat Amount with Historical Cost and Current Value - Rahim, Syamsuri; Maimuna, Yuni (STIEM BONGAYA, 2021)
This study aims to analyze and compare historical cost and current value as the basis for asset valuation in determining the amount of zakat of a company. This research was conducted at the Makassar Branch of the Indonesia Stock Exchange. The researcher also visited the official website of the Indonesia Stock Exchange (www.idx.co.id) and the official website of the Financial Services Authority for the Sharia Capital Market (www.syariah.ojk.go.id). The research was carried out in approximately 2 months, starting from August 2020 to September 2020. This study uses quantitative data methods. This study using a case study approach. The data source used in this study is secondary data obtained from the company's published financial statements taken from the Indonesia Stock Exchange. The results show that the calculation of corporate zakat is still experiencing difficulties because there are different calculation formats and different elements of financial statements between the current standard format and the fiqh language due to lack of socialization to the company, and almost all calculation methods show more significant results when the assets are valued using current values